Le don/contre-don à l'épreuve d'un dispositif tutoral : des conséquences dans le domaine de la pédagogie universitaire ? - Alain Baudrit
A tutorial system set up at the Medicine School in Bordeaux University reveals practices similar to the gift/counter-gift trading system observed by the anthropologist Marcel Mauss in many Archaic societies. In fact, students tend to give back what they have received. Helped in the first year of medical school by more advanced students in the curriculum, they then volunteer to help the freshmen, a process that is renewed each new academic year. These appearances may be misleading given the competitive environment of medical education and given the fact that archaic societies and modern societies are not the same thing. This is the issue raised in this article, which is based on work on psychological states, identity processes and the image that people who receive help and support from others have of themselves or, conversely, who provide assistance and support to others. This is a leading question for pedagogical deciders in universities, whose role consists among others in establishing procedures that help limit the number of students who fail in the first years of their curriculum.